Tunability of the free-spectral range by microwave injection into a mid-infrared quantum cascade laser - Rodriguez, Etienne (2021)
The free-spectral range (FSR) of quantum cascade lasers (QCLs) emitting at 4.7 µm can be tuned through direct microwave modulation. The intrinsic short carrier lifetime of inter-subband transitions, along with impedance matched electrical packaging, allows a high-speed modulation up to more than 30 GHz. A significant broadening and flattening of the lasing spectrum is observed under radio frequency (RF) injection with frequencies close to the round-trip cavity. An accurate analysis of the high resolution spectra of the laser shows a comb-like regime for both free-running and RF modulated QCLs, if the modulation frequency is within the locking-range of the device. One of the main advantages of collecting high-resolution mid-infrared spectra, over the plain investigation of the beatnote in the microwave region, is the access to all the longitudinal modes and thus the accurate measure of the FSR over the whole optical spectrum. The use of high-resolution spectroscopy provides an in-depth and comprehensive analysis of lasing spectra under microwave modulations.